Peningkatan Kualitas Pembelajaran Keterampilan Berbicara Bahasa Indonesia melalui Teknik Bercerita (Penelitian Tindakan Kelas Pada Siswa Kelas VII-3 SMPN 13 Bandar Lampung Tahun Pelajaran 2022/2023) - Meliyanti, Meliyanti (STKIP PGRI Bandar Lampung, 2023)
The ability to speak is one of the language skills that a person needs to have. That is someone who lives in the community and school environment and anywhere. Speaking is common to us, but the failure of learning speaking skills is still widely heard among schools. This study used a classroom action research method that lasted for three months, carrying out various activities. The results possessed in learning Indonesian speaking skills through storytelling techniques can increase, this can be seen from the results of the pre-test nlai average children 40.5 while in the results of the children's test 77.15, and cycle 1 children get an average score of 63.3 and cycle II an average of 73.58. The above improvement can be seen that learning Indonesian language skills through storytelling techniques at SMPN 13 Bandar Lampung can increase, this shows that storytelling techniques are feasible and can be used to be applied in schools because they provide good results, especially in speaking skills.